SAT0539 The Risk of Future Attacks in Patients with Incident Gout: a Population-Based. (23rd January 2014) - Bongartz, T.; Zleik, N.; Clement, M.; Khun, H.; Crowson, C.; Matteson, E.
Abstract : Objectives: While there appears to be consensus that non-pharmacological uric acid lowering therapies (diet and lifestyle modifications) should be initiated in every patient presenting with gout, there is much less agreement as to when urate lowering drugs should be considered. Expert opinion ranges from starting uric acid lowering therapy after the first attack of gouty arthritis through a more cautious approach where therapy is only started in patients with more than 3 attacks per year. We aimed to assemble a population based cohort of patients with newly diagnosed gout to determine the risk of additional flares after an initial gout attack and explore the role of various demographic, clinical and laboratory predictors that may aid the clinician in quantifying this risk. Methods: We examined a population-based incidence cohort of patients with gout, diagnosed according to the New York, Rome or ACR preliminary criteria. All subjects were followed longitudinally through their complete community medical records, until death, migration or July 1 st 2012. We used a conditional frailty model (accounting for multiple flares per subject) to explore risk factors of subsequent flares. Results: 46 patients with incident gout were followed for a mean (SD) of 12.9 (8.6) years. The majority of patients were male (70%) and the mean age (SD) at gout onset was 66.0 (14.8) years. Isolated podagra was the most common form of joint involvement at disease onset (72%). The mean (SD) serum uric acid level was 8.1 (2.2) mg/dl. 28 patients (61%) developed at least 1 subsequent flare, with a total of 101 subsequent flares during the entire follow-up period. Patients with the highest risk of subsequent flares had an initial joint involvement other than first MTP joint (odds ratio 3.9, 95% CI 1.03, 14.77) and a high serum uric acid level at baseline (OR 1.69, 95% CI 1.26, 2.27), Age and sex were not significant predictors of subsequent flare risk. Conclusions: The majority of patients in our population-based cohort did develop at least one subsequent flare after an initial diagnosis of gout. Joint involvement other than the first MTP joint and serum uric acid level were significant predictors of subsequent flares and should be taken into account when deciding on the timing of uric acid lowering therapy. Disclosure of Interest: None Declared